Exploring the impact of school field experience on prospective English teachers’ readiness - Rachel; Panggua, Selvi; Siumarlata, Viktor; Patandung, Yosef (Indonesian Research Journal in Education |IRJE|, 2025)
This research investigates how the Program Pengenalan Lapangan or PLP (the School Field Experience Program) influences English teacher candidates’ preparedness. Using a 22-item questionnaire, data were collected from 41 participants through a quantitative descriptive method. Results show that 78.71% believe the school field experience program enhanced their readiness, particularly in instructional planning, classroom management, communication, and character development. The high percentage of positive responses suggests that the school field experience program effectively bridges theory and practice. However, lower parental communication and administrative task scores indicate aspects needing improvement. The research highlights the value of experiential learning in teacher education and suggests enhancing the program through reflective teaching and stronger mentorship.